Fundamentals of corporate finance - Brealey, Richard A. 1936-; Myers, Stewart C. 1940-; Marcus, Alan J. (McGraw-Hill/Irwin, 2007)
Fundamentals of Corporate Finance uses a modern approach and contemporary examples to present important, often challenging topics in efforts, and maket-leading finance textbooks, it's no surprise that authors Brealey, Myers and Marcus have created an innovative, market-driven revision that's more student-friendly than ever.
Includes bibliographical references and index
Keywords: Bedrijfsfinanciën; Corporations -- Finance; Management; Corporate Finance; Finanzierungstheorie; Finanzierung; Lehrbuch